Mechanical behaviour of photovoltaic composite structures: A parameter study on the influence of geometric dimensions and material properties under static loading. (September 2017) - Aßmus, M.; Bergmann, S.; Naumenko, K.; Altenbach, H.
Abstract: Photovoltaic modules available on the market are subject to a wide variety of geometric dimensions and material properties. During their service life, they are exposed to, among other things, mechanical loads that can affect energy harvesting negatively through mechanically induced damages. Due to the high contrast in mechanical properties and geometric dimensions of constituting materials, classical structural analysis methods for such rather slender structures are unserviceable, what emphasises the necessity of alternative approaches. A potential candidate of that alternatives is the extended layerwise theory. In the present treatise, this theory is used to vary structural parameters in order to gain directions to optimal values of significant geometric and material ratios of constituents, whereby we stay in the range of characteristic parameters for terrestrial photovoltaic modules. The results of the present study constitute characteristic indexes useful in conceptual and design phase when developing photovoltaic modules. Abstract : Highlights: The concept of deformable elastic surfaces is introduced in order to analyse three-layered photovoltaic composite structures. Structural parameters are varied to gain information to optimal values of significant geometric and material ratios. The results constitute characteristic indexes valuable in product development process of photovoltaic modules.